10.9k views
4 votes
What's the tenth term of a sequence with an explicit rule of ƒ(n) = 2 + (–3)(n – 1)?

Question 2 options:

A)

ƒ(10) = –25

B)

ƒ(10) = 27

C)

ƒ(10) = –30

D)

ƒ(10) = 32

2 Answers

6 votes

Answer:

C).ƒ (10) = –25.

Explanation:

User Alexander Kludt
by
5.5k points
5 votes

Answer:

F(10) = -25

Explanation:

To solve an explicit rule, we have to understand every terms in its formula. For a given equation,

F(n) = F(1) + d(n - 1)

Where F(n) = the nth term of the sequence

F(1) = first term

d = common difference

(n - 1) = one term less than the nth term

Note : the above explicit sequence is for arithmetic function.

From the above equation,

F(n) = F(10)

F(1) = 2

d = -3

(n - 1) = (n - 1)

To solve for the 10th term

F(10) = 2 + (-3)(10 - 1)

F(10) = 2 + (-3)(9)

F(10) = 2 + (-27)

F(10) = -25

The 10th term of the sequence is -25

User Dmytro Khmara
by
4.7k points